BIM and big data for construction cost management - Lu, Weisheng; Lai, C. C. (Chi Cheung); Tse, Anthony (London : Routledge, 2019)
"This book is designed to help practitioners and students in a wide range of construction project management professions understand what BIM and big data could mean for them, and how they should prepare to work successfully on BIM-compliant projects and maintain their competencies in this essential and expanding area. In this book, the state-of-the-art information technologies that support high-profile BIM implementation are introduced, case studies show how BIM has integrated core quantity surveying and cost management responsibilities and how big data can enable informed decision-making for cost control and cost planning. The authors combined professional and academic experience demonstrates, with practical examples, the importance of using BIM and particularly the fusion of BIM and big data, to sharpen competitiveness in global and domestic markets. This book is a highly valuable guide for people in a wide range of construction project management and quantity surveying roles. In addition, implications for project management, facilities management, contract administration and dispute resolution are also explored through the case studies making this book essential for reading for built environment and engineering professionals"--
Introduction -- BIM theories and technologies -- BIM implementation strategies, prospects, and challenges -- Adopting BIM for cost management -- Case studies -- Big data for construction cost management -- Current challenges and future outlooks -- Good practices for adopting BIM for cost management -- The future of BIM and big data in quantity surveying -- Conclusion.
OCLC-licensed vendor bibliographic record.
Keywords: Building -- Cost control -- Data processing; Building -- Estimates -- Data processing; Building information modeling; Big data; TECHNOLOGY & ENGINEERING / Civil / General; ARCHITECTURE / Reference; ARCHITECTURE / Professional Practice